The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s00167-020-06392-9
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells and platelet-rich plasma promote tendon allograft healing in ovine anterior cruciate ligament reconstruction

Abstract: Purpose The effect of bone marrow mesenchymal stromal cells (BMSCs) and platelet-rich plasma (PRP) on tendon allograft maturation in a large animal anterior cruciate ligament (ACL) reconstruction model was reported for the first time. It was hypothesised that compared with non-augmented ACL reconstruction, BMSCs and PRP would enhance graft maturation after 12 weeks and this would be detected using magnetic resonance imaging (MRI). Methods Fifteen sheep und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…19,41 Graft healing after ACLR consists of 2 main biological processes: tendon-bone healing and intra-articular graft remodeling. 25,41,49,52 An understanding of these 2…”
mentioning
confidence: 99%
“…19,41 Graft healing after ACLR consists of 2 main biological processes: tendon-bone healing and intra-articular graft remodeling. 25,41,49,52 An understanding of these 2…”
mentioning
confidence: 99%
“…In the sheep model described by Hexter et al in 2020, the authors observed that BMSCs and PRP significantly enhanced graft maturation, indicating that orthobiologics might accelerate biological events related to tendon allograft incorporation [72]. They also found that femoral tunnel expansion was significantly correlated with inferior maturation of the intra-articular graft.…”
Section: Discussionmentioning
confidence: 96%
“…It is important to highlight the discrepancy between 2 recent articles: one on an experimental study stating that orthobiologics can accelerate biological events related to tendon allograft incorporation [72] and another on a clinical study on meniscal repair in the ACLR setting stating that the added use of intraoperative PRP does not improve the analyzed parameters (self-reported knee function, functional performance, and time to return to previous activity). According to Hexter et al, the use of PRP might have negative consequences for the postoperative recovery of knee range of motion [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9]16,30,37 PRP has had great success in accelerating ACL healing in animal models. 3,10 However, clinical studies using human participants to investigate the effects of PRP on ACLR have shown inconsistent clinical outcomes. Mahdi and Hatem 16 reported that PRP was a safe procedure that enhanced graft-bone integration at 12 weeks' follow-up after ACLR.…”
mentioning
confidence: 99%